Vitamin D3 as adjuvant in the treatment of type 2 diabetes mellitus: modulation of genomic and biochemical instability. (6th February 2019) - Fagundes, Gabriela Elibio; Macan, Tamires Pavei; Rohr, Paula; Damiani, Adriani Paganini; Da Rocha, Franciani Rodrigues; Pereira, Maiara; Longaretti, Luiza Martins; Vilela, Thais Ceresér; Ceretta, Luciane Bisognin; Mendes, Carolini; Silveira, Paulo Cesar Lock; Teixeira, João Paulo Fernandes; et al.
Abstract: Type 2 diabetes mellitus has undergone a worldwide growth in incidence in the world and has now acquired epidemic status. There is a strong link between type 2 diabetes and vitamin D deficiency. Because vitamin D has beneficial effects on glucose homeostasis, the aim of this study was to evaluate the influence of vitamin D3 supplementation on the modulation of glycaemic control and other metabolic effects, as well as modulation of genomic instability in patients with type 2 diabetes. We evaluated 75 patients with type 2 diabetes, registered in the Integrated Clinics of the University of Southern Santa Catarina. Participants received 4000 IU of vitamin D3 (25(OH)D) supplementation daily for 8 weeks. Blood samples were collected at the beginning and at the end of the supplementation, and 4 weeks after the end of supplementation. The glycidic and lipid profiles [total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein and triglycerides], oxidative stress, DNA damage and 25(OH)D levels were evaluated. Vitamin D3 supplementation for 8 weeks showed enough to significantly increase blood levels of 25(OH)D. A significant difference in lipid profile was observed only in non-HDL cholesterol. Significant changes were observed in glucose homeostasis (fasting glucose and serum insulin) and, in addition, a reduction in the parameters of oxidative stress and DNA damage. There was a significant reduction in the values of 25(OH)D 4 weeks after the end of the supplementation, but levels still remained above baseline. Use of vitamin D supplementation can be an ally in the health modulation of patients with type 2 diabetes mellitus.